Parents' Involvement in Early Childhood Education - Yunus, Saima; Khan, Fahad Munir; Khan, Abdul Ahad Munir; Khan, Maaz Munir; Khan, Abdur Rafay Munir (2025)
LAMIC countries would benefit substantially from early childhood education (ECE) programs because these programs assist disadvantaged children to achieve their full potential according to research findings. These educational programs continue to receive insufficient research regarding their effects on child mental health and comprehensive welfare development. Parents enable fundamental growth in their children during their early years. The involvement of parents brings enduring changes to their children's capability to learn. The correct stimulation of children during early childhood years from birth through age five leads to stronger academic performance in the future. The research examines how parents as well as instructors in Pakistani early childhood education and care institutions think about and interact with their roles. The research shows how parental influence affects government legislation because current policy development lacks adequate parental input.